INOVASI MEDIA PEMBELAJARAN GAME QUARTET CARD PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP - Anggraini, Novia Afriana; Santia, Ika; Hima, Lina Rihatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to develop quartet card learning media on flat-sided space building material. This research uses the Research and Development (R&D) method with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques used are interviews, questionnaires, and observations. The validity of the quartet card learning media is seen from the results of the expert validation test with a percentage score obtained of 89.6% from media experts, 81.3% from material experts, and 92.3% from practitioners who are included in the category of very valid learning media can be used without revision. The results of student responses on small-scale trials obtained a percentage of 82% and large-scale trials obtained a percentage of 83% with a very interesting category, meaning that the attractiveness of quartet card learning media is very good. The quartet card learning media is declared valid and interesting to use in learning mathematics on flat-sided space building material.